Muslim Travellers: A Bibliometric Analysis - Syadiyah Abdul Shukor; Uraiporn Kattiyapornpong (Emerald Publishing, 2024)
Purpose This study aims to provide an insight into research related to Muslim travellers in the past 42 years. Design/methodology/approach Using 342 articles collected from the Scopus database from 1981 to 2023, this study adopted the Bibliometrix in RStudio package and Biblioshiny Web application to analyse the research on Muslim travellers in two main categories: overview and intellectual structures. Findings The first publication related to Muslim travellers occurred in 1981 and number of publications remained few in the first three decades. Starting 2015, publications on Muslim travellers experienced a growing development of discussions and publications. Four prominent research clusters were identified: “halal tourism”, “hajj”, “Islamic tourism” and “tourist post-purchase”. Themes within the research on Muslim travellers have evolved from the “pilgrimage” to “Islamic tourism” theme. Then, the “Islamic tourism” theme has been expanded to a variety of topics that were primarily relevant to Muslim tourist behaviour. Themes related to “climate change” and “Syria” have been identified as the niche themes that need further study. Research limitations/implications Scopus database is regularly updated as the number of papers and journals may increase or decrease from time to time. This may impact on the fluctuation of the theme analysis from the article search at that time. Originality/value This study reviews publications related to Muslim travellers over the past four decades. Accordingly, it can aid interested researchers and stakeholders in gaining a more thorough understanding of Muslim traveller research